Poly(vinylidene fluoride) nanofibrous mats with covalently attached SiO 2 nanoparticles as an ionic liquid host: enhanced ion transport for electrochromic devices and lithium-ion batteries - Zhou, Rui (2016)
In this article, it is demonstrated that the electrospun poly(vinylidene fluoride-co-hexafluoropropylene) (P(VDF–HFP)) nanofibrous mat functionalized with (3-aminopropyl)triethoxysilane is a versatile platform for the fabrication of hybrid nanofibrous mats by covalently attaching various types of inorganic oxide nanoparticles on the nanofiber surface via a sol–gel process. In particular, SiO2-on-P(VDF–HFP) nanofibrous mats synthesized using this method is an excellent ionic liquid (IL) host for electrolyte applications. The IL-based electrolytes in the form of free-standing mats are obtained by immersing SiO2-on-P(VDF–HFP) mats in two types of liquid electrolytes, namely LiClO4/1-butyl-3-methylimidazolium tetrafluoroborate and bis(trifluoromethane)sulfonimide lithium salt/1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide. It is found that the surface attached SiO2 nanoparticles can effectively serve as salt dissociation promoters by interacting with the anions of both ILs and lithium salts through Lewis acid–base interactions. They dramatically enhance the ionic conductivity and lithium transference number of the electrolytes. In addition, better compatibility of the electrolytes with lithium electrodes is also observed in the presence of surface-attached SiO2. Using IL-loaded SiO2-on-P(VDF–HFP) nanofibrous mats as the electrolytes, electrochromic devices display higher transmittance contrast, while Li/LiCoO2 batteries show significantly improved C-rate performance and cycling stability. This class of novel non-volatile electrolytes with high ionic conductivity also has the potential to be used in other electrochemical devices.